Sarcasm, Irony, and Manipulation: Non‑Observance of Gricean Maxims in Teenage Interaction in Mean Girls (2004) - Rihmatul Marhamah; Virgia Eldiana; Cecep Agus (Journal of Innovative and Creativity, 2026)
Conversational maxim non-observance frequently occurs in adolescent interactions and plays a significant role in constructing implied meaning in everyday communication. This study examines the use of Gricean maxim non-observance in the film Mean Girls (2004) by focusing on how characters employ flouting, violation, and opting out strategies to negotiate power, humor, and social positioning. Unlike previous studies that mainly emphasize the identification and frequency of maxim violations, this research highlights the pragmatic functions underlying non-observance in competitive teenage discourse. The study employed a qualitative descriptive method using the film script as the primary data source. Data were collected through documentation and note-taking techniques, resulting in 16 utterances containing non-observance of conversational maxims. The findings show that flouting is the most dominant type with 11 cases (68.8%), followed by violations with 4 cases (25%) and one instance of opting out (6.3%). Flouting the maxim of Quality is commonly used to express sarcasm and indirect criticism, while violations function as tools of manipulation and false politeness. Opting out serves as a face-saving strategy in certain interactions. These findings indicate that maxim non-observance functions as a pragmatic strategy to maintain dominance, reinforce exclusion, and manage social relationships among adolescent peer groups.